Transcytosis via the late endocytic pathway as a cell morphogenetic mechanism. (13th July 2020) - Mathew, Renjith; Rios‐Barrera, L Daniel; Machado, Pedro; Schwab, Yannick; Leptin, Maria
Abstract: Plasma membranes fulfil many physiological functions. In polarized cells, different membrane compartments take on specialized roles, each being allocated correct amounts of membrane. The Drosophila tracheal system, an established tubulogenesis model, contains branched terminal cells with subcellular tubes formed by apical plasma membrane invagination. We show that apical endocytosis and late endosome‐mediated trafficking are required for membrane allocation to the apical and basal membrane domains. Basal plasma membrane growth stops if endocytosis is blocked, whereas the apical membrane grows excessively. Plasma membrane is initially delivered apically and then continuously endocytosed, together with apical and basal cargo. We describe an organelle carrying markers of late endosomes and multivesicular bodies (MVBs) that is abolished by inhibiting endocytosis and which we suggest acts as transit station for membrane destined to be redistributed both apically and basally. This is based on the observation that disrupting MVB formation prevents growth of both compartments. Synopsis: Cells reorganize their plasma membranes to build complex structures. This study shows that the endocytic pathway is required for proper membrane allocation during epithelial tube morphogenesis in Drosophila, with late endosomes acting as hubs for membrane and protein redistribution. Subcellular tubulogenesis in embryonic trachea uses apical‐to‐basal transcytosis to distribute plasma membrane to the appropriate domains of the growing tube branch. Dynamin‐mediated apical endocytosis is required for apical membrane pruning, thereby providing material that allows the basal compartment to grow. Proteins targeted to the basal compartment transit from the apical to the basal compartment through late endosomes. Late endosomes are also required for the recycling of material back to the apical compartment. Abstract : Late endosomes act as hubs to regulate membrane material allocation during epithelial tube morphogenesis in the Drosophila tracheal system.